REKAYASA NILAI DAN ANALISIS DAUR HIDUP PADA MODEL ALAT POTONG KUKU DENGAN LIMBAH KAYU DI CV. PIRANTI WORKS - Santoso, Haryo; Ronald, Ronald (Departemen Teknik Industri, Fakultas Teknik, Universitas Diponegoro, 2012)
Produk-produk yang menggunakan bahan polystyrene dengan jenis extruded polystyrene (PS) merupakan salah satu sumber pencemaran bagi lingkungan dan kesehatan manusia. Salah satu kandungan yang terdapat pada polystyrene adalah karsinogen yang dapat menyebabkan kanker. Kandungan karsinogen akan terurai selama 100 tahun pada tanah dan 7 tahun pada tubuh manusia Penelaahan kembali desain dan melakukan substitusi material menggunakan pendekatan rekayasa nilai (value engineering) dan analisis daur hidup dapat menghasilkan produk dengan nilai atau value yang lebih baik. Rekayasa nilai merupakan suatu metoda yang didasarkan pada pemahaman bahwa fungsi yang disandang oleh sebuah produk merupakan kunci untuk mencapai nilai yang lebih baik, sedangkan analisis daur hidup bertujuan mengevaluasi dampak lingkungan dari suatu produk dan menurunkan pertanggungan terhadap lingkungan. Pemanfaatan limbah di CV. Piranti Works pada model alat potong kuku dengan mengintegrasikan rekayasa nilai dan analisis daur hidup bertujuan untuk memberikan nilai atau value yang lebih baik dari segi lingkungan, serta sebagai langkah awal mengurangi penggunaan polystyrene. Hasil dari penelitian ini akan menunjukkan bahwa limbah kayu pada CV. Piranti Works dapat dioptimalkan serta memberikan nilai tambah dan layak untuk menggantikan bahan polystyrene secara lingkungan, sekaligus visi perusahaan yang menuju arah sustainabilitas dapat tercapai. Kata Kunci : rekayasa nilai, analisa daur hidup, polystyrene, alat potong kuku. Abstract Products that use materials polystyrene with the type of extruded polystyrene (PS) is one source of pollutan to the environment and human health. One of the content contained on polystyrene is a carsinogens that can cause cancer. The content of carsinogens will decompose over 100 years on land and 7 years in human body. Review of re-design and material substitution using value engineering aprroach and life cycle analysis can produce products with a value or a better value. Value engginering is a method that is based on the understanding that the functions carried by a product is key to achieving better value, while life cycle analysis to evaluate the environmental impacts of a product and reduce the coverage of the environment. Utilization of waste in the CV. Piranti Works nail on the model of cutting tools by integrating value engineering and life cycle analysis aimed to provide value or a better value in terms of environment, as well as an intial step to reduce the use of polystyrene. The results of this study will show that the waste timber in CV.Piranti Works can be optimized as well as providing added value and worth to replace polystyrene materials in the environment, an the company’s vision toward sustainability can be achieved. Analysis of the eco-efficiency in CV. Piranti Works where this is a green industry, is based of life cycle analysis of the production. LCA analysis is used to evaluate the environmental impacts of wooden radio product also improve of resource usage efficiency and reduce coverage on the environment. In addition to LCA as environmental parameters are also contained an analysis of economic parameters by using cost benefit analysis and market analysis. In addition this research is to integrating economic and environmental parameters that form the eco-efficiency also integrate social parameters, where the integration of these three parameters lead to the sustainability analysis of wooden radio product. The results of this study will proof that the eco-efficiency of production can show the feasibility of an economically and environmentally, and implementation of eco-efficiency strategies can add value both economically, socially, and environmentally. Keyword : value engineering, life cycle analysis, polystyrene, nails cutting tools